PENGEMBANGAN ALAT PERMAINAN JUMP NUMBERS UNTUK MENINGKATKAN KEMAMPUAN MENGENAL ANGKA PADA KELOMPOK B DI TK MUTHIAH ISLAMIC SCHOOL (MIS) KAYUAGUNG - Fadhilah Rahmadani; Nyayu Soraya; Adi Bahtiar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the lack of use of learning media in introducing numbers at Muthiah Islamic School (MIS) Kayuagung, which affects the low interest in learning among students. The purpose of this research is to develop a jump numbers game tool to introduce numbers and animals to early childhood. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research are the students of class B1 at Muthiah Islamic School (MIS) Kayuagung. Data collection techniques used are observation, interviews, questionnaires, and documentation, while data analysis techniques involve validity, practicality, and effectiveness tests. The results of the validity test show that the playing tool is categorized as very valid: material expert (95%) and media expert (92.8%), the practicality test by expert practitioners using a questionnaire obtained a score of 86% categorized as very practical, and the response questionnaire from students in a small-scale trial was 92.2% stated as very practical, and in a large-scale trial, it was 96% stated as very practical. The effectiveness test of the jump numbers playing tool was seen in the hypothesis test using the t-test, which resulted in a significance of 0.000 < 0.05, which means H0 is rejected and Ha is accepted, indicating a significant influence in the use of the jump numbers playing tool to introduce numbers at Muthiah Islamic School (MIS) Kayuagung. The results of this study conclude that the jump numbers playing tool for introducing numbers is declared valid, practical, effective, and worthy of use in learning.